"The Lucky country"? A critical exploration of community gardens and city–community relations in Australian cities. Issue 8 (3rd August 2017) - Thornton, Alec
ABSTRACT: Urban agriculture (UA) has the potential to expand beyond the grassroots level to meet the social, cultural, economic and food needs of urban dwellers. At its core, UA represents an alternative use of urban space that occurs with or without government support or approval. The experiences of community gardeners and their views of, and engagement in, community gardens as a form of UA, or local "alternative food networks", is a focal point of this paper. Relying on Australian city case studies, this paper explores community gardens, using critical urban approaches concerning "rights to the city" and diverse economies. Findings from this study reveal how community gardeners understand and participate in diverse economies and extended local food networks. They also identify respondents' views of local councils as barriers to the emergence of community gardens, and other forms of UA, as a local response to growing concerns over impacts of the global food chain on food security. In contrast to other Western cities, effective city–community relations for community garden growth have yet to emerge in Australian cities, as key policy areas for urban sustainability and social cohesion.